Partial Proteome Map of Campylobacter Jejuni Strain Nctc11168 by Gel-Free Proteomics Analysis - Shi, Zilun; Dawson, Chris; On, Stephen L.W.; Hussain, Malik Altaf (International Journal of Applied Sciences and Biotechnology, 2014)
A proteome map of the foodborne pathogen Campylobacter jejuni NCTC11168 was analyzed using a state-of-the-art gel-free proteomic approach for the first time. A whole cell protein extract was prepared from the C. jejuni strain NCTC11168 grown in brain heart infusion (BHI) broth at 42°C under microaerobic conditions. A gel-free technique using isobaric tags for relative and absolute quantitation (iTRAQ) was employed to create a protein expression profile of the strain. Liquid chromatography-mass spectrometry (LC-MS/MS) was used to identify the proteins. Protein functionalities were searched to classify them. A total of 235 proteins were identified in the whole cell protein fraction of C. jejuni NCTC11168 cells using iTRAQ analysis. Functional grouping of the identified proteins showed that forty percent of these proteins were associated with energy metabolism, protein synthesis and genetic information processing. iTRAQ was faster, easier and proved more sensitive than two-dimensional gel-based proteomics approaches previously applied to C. jejuni, making it an attractive tool for further studies of cellular physiological response. DOI: http://dx.doi.org/10.3126/ijasbt.v2i4.11253  Int J Appl Sci Biotechnol, Vol. 2(4): 464-477